Crystallization of GeO2 thin films into α-quartz: from spherulites to single crystals. (15th August 2021) - Zhou, Silang; Antoja-Lleonart, Jordi; Nukala, Pavan; Ocelík, Václav; Lutjes, Nick R.; Noheda, Beatriz
Abstract: Piezoelectric quartz (SiO2 ) crystals are widely used in industry as oscillators. As a natural mineral, quartz and its relevant silicates are also of interest in geoscience and mineralogy. However, the nucleation and growth of quartz crystals are difficult to control and not fully understood. Here we report successful solid-state crystallization of thin film of amorphous GeO2 into quartz on various substrates, including Al2 O3, MgAl2 O4, MgO, LaAlO3 and SrTiO3 . At relatively low annealing temperatures, the crystallization process is spherulitic: with fibers growing radially from the nucleation centers and the crystal lattice rotating along the growth direction with a linear dependence between the rotation angle and the distance to the core. For increasingly higher annealing temperatures, quartz crystals begin to form. The edges of the sample play an important role in facilitating nucleation followed by growth sweeping inward until the whole film is crystallized. Control of the growth allows single crystalline quartz to be synthesized, with crystal sizes of hundreds of microns achieved on sapphire substrates, which is promising for further piezoelectric applications. Our study reveals the complexity of the nucleation and growth process of quartz and provides insight for further studies. Graphical abstract: Image, graphical abstract